2015
DOI: 10.1111/1348-0421.12258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the presence of reduced nicotinamide adenine dinucleotide phosphate in bacterial metabolites used as immunostimulators and its role in nitric oxide induction

Abstract: Bacterial metabolites that act as immunostimulators have aroused interest because of their therapeutic potential in several immune disorders. These metabolites are complex, heterogeneous, and comprise numerous immune-boosting biomolecules. To better understand their immune stimulatory properties, characterization of their components is essential. An ether extract of metabolites from nine bacterial species was analyzed for the presence of reduced nicotinamide adenine dinucleotide phosphate (NADPH) or other fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The nonspecific immune stimulatory drug used in this study was manufactured and supplied by M/s Union Drugs Co. Ltd., Kolkata, India under the trade name “Sterodin.” It is constituted of an ether extract of nine bacterial metabolites in combination with solvent extracts of ox bile lipids. Composition of the final aqueous solution has been described earlier (Singh and Bhattacharyya, , , ).…”
Section: Methodsmentioning
confidence: 99%
“…The nonspecific immune stimulatory drug used in this study was manufactured and supplied by M/s Union Drugs Co. Ltd., Kolkata, India under the trade name “Sterodin.” It is constituted of an ether extract of nine bacterial metabolites in combination with solvent extracts of ox bile lipids. Composition of the final aqueous solution has been described earlier (Singh and Bhattacharyya, , , ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, extensive characterization of the cloned and purified MRA2164 protein under different experimental conditions has clearly showed that it is functionally very similar to NirK protein known to be present in other bacteria (Figs. 4 , 5 , S4 ) 36 38 . The Km of this enzyme was found to be ~ 17 mM, which justifies the level of NO produced at > 5 mM of nitrite in the medium (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…4C). [37][38][39][40] Additionally, no signicant signal was observed aer the MP-CMSA probe was incubated with non-BLA-expressing E. coli ATCC 25922, that is the Clinical and Laboratory Standards Institute (CLSI) recommended negative quality control strain. 41 Comparatively, a remarkable MS signal can be detected in three clinically prevalent BLA-expressing bacterial strains including K. pneumonia/KPC-3 ATCC BAA-2814, K. pneumonia/SHV-18 ATCC 700603 and E. coli/TEM-1 ATCC 35218 (Fig.…”
Section: Ultrasensitive and Specic Detection Of Bla-associated Drbmentioning
confidence: 99%